KAJIAN YURIDIS PENETAPAN PERMOHONAN ISBAT NIKAH DI PENGADILAN AGAMA WATAMPONE KELAS I.B - nurhidayah, Nurhidayah (Jurnal Ar-Risalah, 2021)
The number of application on marriage legalization in the last two years in the Religious Watampone Class I.B has been quite high. This is due to the high demands of people to legalize their marriage for certain reasons, such as divorce proceedings for an undocumented marriage, administrative requirements to get children’s birth certificate, TASPEN (retirement funds) administration, passport registration, getting veteran widow's pension, and publication ofmarriage certificate due to underhand marriage.Regarding the marriage legalization cases in the Religious Court Class I.B of Watampone, if the formal requirements have been met, then the religious court by the judges will make a verdict or decision of which written "the applicationis approved". Meanwhile, if the formal requirements are not met, then the judge will make a verdict or decision declaring that "the application is overruled". Judge in deciding a case will look and pay attention on posita (case, the actual fact) and should be in accordance with existing procedures, among others, present witnesses at the hearing and show that there is evidence for consideration. The judge, of course, will put forward maqasid syari’ah (the objectives of sharia),so that the impact will be on the benefit of generations, to keep and maintain the honor that will be seen in the decision or verdict of the judge who accepted and granted other. Therefore, marriage legalization in principle is one of the legal protection and legal certainty, as referred to in Article 7 KHI, toward a marriage that cannot be proven with a marriage certificate as an authentic document in accordance with the mandate of Marriage Act, which requires that every marriage shall be recorded by state institutions.